UNDERSTANDING THE IMPACT OF PCOS ON WOMEN'S QUALITY OF LIFE: A SCOPING REVIEW - Setyawati, Anita; Nuraeni, Rina; Solichah, Nur Umi Aminatus (Ikatan Perawat Maternitas Indonesia Provinsi Jawa Barat, 2025)
Approximately 25% of women of reproductive age worldwide are affected with polycystic ovarian syndrome (PCOS). A number of research have concentrated on evaluating the quality of life of women diagnosed with PCOS and related health issues. This study was undertaken to assess the quality of life in women with PCOS. This research constitutes a scoping review grounded in the Arksey and O'Malley paradigm. A systematic literature search was performed in CINAHL Plus with Full-Text, PubMed, and Scopus utilising the search phrases